‘They just told me to go to theatre’: women’s experiences and support needs following emergency caesarean section in Kawempe National referral hospital, Uganda - Charles Taban LoPoni; Joseph Rujumba; Wycliffe Ssekatawa; Martyn Adupet; Jolly Beyeza Kashesya; Ismail Sule; Miriam Nakalembe (BMC Pregnancy and Childbirth)
Abstract Background Globally, the Caesarean Section (CS) rate is estimated at 21.1% and tripled from 7% in 1990 and projected to reach 28.5% by 2030. In Kawempe National Referral Hospital (KNRH) in Kampala, Uganda, 43.0% of women gave birth by CS in 2022 and 95% of the procedures were emergency caesarean sections (EmCS). The experiences and support needs of women following CS, however, were not explored, despite knowledge of challenges associated with CS compared to vaginal birth (VB). Objective To explore the experiences and support needs of women following emergency caesarean section in Kawempe National Referral Hospital. Methods A phenomenological inquiry was conducted in the postnatal clinic of KNRH among women six weeks following EmCS and health workers as Key informants (KIs) in KNRH. In-depth audio-recorded interviews with women after CS and KI interviews were conducted. The audio records were transcribed verbatim and analysed using deductive, but largely inductive thematic techniques. Results Twenty in-depth interviews and six KI interviews were conducted between June and July 2023. Average age of the women was 27.95 years. Most women highlighted negative experiences such as fear of losing their lives during surgery, poor pain control and unsatisfactory hospital care such as delays in intervention, poor communication, feelings of discrimination and neglect and informal hospital charges. Conversely, successful surgery that saved their lives and that of their babies, presence of a companion after CS and confidence in qualified staff in the national referral hospital were also highlighted. Both women and KIs expressed needs for adequate pre-operative care, financial resources, adequate pain control and quality time for interaction with health care providers to improve care after EmCS. Conclusion Following EmCS, women have both positive and negative experiences at individual, relationship and health care levels. Positive experiences include successful surgery, presence of a companion and being managed in a national referral hospital. Negative experiences, however, included fear of death for mother and baby, poor pain control, poor communication and informal hospital charges. Financial support, companionship after CS and information on indications for surgery and other interventions were the support needs expressed by the women.